EVALUATION OF IN VITRO IMMUNOMODULATORY ACTIVITY OF AQUEOUS AND ETHANOLIC EXTRACT OF EULOPHIA NUDA LINDL - Kanase, Vanita; Patil, Diptesh T (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to evaluate the in vitro immunomodulatory activity of aqueous and ethanolic extract of dried tubers of Eulophia nuda. Methods: Effect of both the extracts was evaluated at various concentrations (832–6.5 μg/ml) for secretion of mediators such as nitric oxide (NO), superoxide, lysosomal enzyme, and myeloperoxidase activity of isolated murine peritoneal macrophages. Results: The extracts showed stimulation of NO, statistically significant at 832 μg/ml (SI 1.739) for ENA and at 832 μg/ml (stimulation index [SI] 1.662) for ENE; significant stimulation on lysosomal enzyme release for ENA at 832 μg/ml (SI 1.404) and ENE at 832 μg/ml (SI 1.513); myeloperoxidase activity was statistically significant for ENA at 832 μg/ml (SI 1.728) and ENE at 832 μg/ml (SI 1.770). Conclusion: In vitro phagocytic index showed significant results and thus proving the need for confirmation through in vivo studies.